(untitled) (Research, Society and Development, 2025)
The Pharmacotherapeutic Monitoring service (FA) works to detect, prevent and resolve Problems RElated to the use of Medicines (PRM). This study aims to evaluate the impact of the PA service on elderly people with diabetes and/or high blood pressure treated at a Basic Pharmacy in Diamantina. This study is longitudinal, with before and after assessment. For the study, pharmaceutical consultations were carried out with people over 60 years of age, both sexes, patients with Systemic Arterial Hypertension (SAH) and/or Diabetes Mellitus (DM), users of three or more continuous medications and who had three or more pharmaceutical consultations in the studied interval. 30 patients participated, the average age was 69.7 years, 56.7% were women, 97% were hypertensive and 50% were diabetic. Around 80% used between 5 and 10 medications. 136 pharmaceutical consultations were carried out. There was a 10% increase in the number of patients with controlled systolic blood pressure. 82.4% of the 68 (PRM) were resolved, the most frequent being “medication non-adherence”. Of the 42 Negative Results associated with Medications (RNM), 85.7% were resolved, with “quantitative ineffectiveness” corresponding to 50% of cases. 107 pharmaceutical interventions were carried out, with “health education” being the most frequent. The DRPs and RNMs detected were, for the most part, resolved by interventions carried out by the pharmacist, showing their importance in health education in the care of the elderly in primary care.